The genus Hylebainosoma Verhoeff, 1899 (Diplopoda, Chordeumatida, Haaseidae): Redescription of Hylebainosoma tatranum, description of a new troglobiont species and notes to the Hylebainosoma–Romanosoma species group - Tajovský, Karel; Mock, Andrej; Papáč, Vladimír (Zootaxa, 2014)
A revision of the taxonomy, distribution and ecology of the millipedes of the genus Hylebainosoma Verhoeff, 1899 in the Carpathians is presented. Based on the study of numerous specimens, we consider the subspecies of the species Hylebainosoma tatranum Verhoeff, 1899 described in the past as overrated, reflecting simply intrapopulational variation attributable to the rather extended area of species distribution, different habitats of its occurrence (surface and cave habitats, soil, litter and stony debris) and wide altitudinal range from the forest zone in foothills to the alpine zone above timberline. Besides the redescription of males, the morphology of female vulvae is presented for the first time. Hylebainosoma tatranum is endemic to the extensive area of the Western and Eastern Carpathians, involving Slovakia, Hungary, the Czech Republic, Poland and highly probably Ukraine. A new troglobiont species from the karst area near the Tisovec Town (Muránska planina Mts., Central Slovakia), Hylebainosoma gulickai n. sp. is described, and is considered as stenoendemic for this small karstic region, with occurrence in few nearby caves. Hylebainosoma gulickai represents the first troglobiont chordeumatid millipede found in the northern territories of the Carpathians and the northernmost troglobiont in Central Europe in general. Morphological characteristics of both males and females are presented. Taxonomic relationships between the closely related genera Hylebainosoma and Romanosoma Ceuca, 1967 are discussed and replacement of the species Hylebainosoma cavernicola (Ceuca, 1967) n. comb., Hylebainosoma oltenica (Ceuca, 1967) n. comb. and Hylebainosoma odici (Ceuca, 1979) n. comb. into the genus Hylebainosoma is proposed. The fourth species described as Romanosoma (?) birtei Ceuca, 1967 we consider as invalid taxon. Romanosoma becomes a junior subjective synonym of the genus Hylebainosoma.